Odpowiedzi

  • Użytkownik Zadane
2010-03-10T19:09:05+01:00
{[a+(a-5)]*3}/2=18 /*2
{[a+(a-5)]*3]=36
3a+3a-15=36
6a=36+15
6a=51 //6
a=8,5 b=8,5-5=3,5
18 3 18
2010-03-10T19:11:25+01:00
P=18cm²=(a+b)razy 1/2 razy h
a podsawa trapezu
a-5 druga podstawa

((a+a-5) razy 1/2) razy 3=18
(1/2a +1/2a-2,5 )razy3 =18
3a-7,5=18
3a=25,5 /:3
a=8,5
8,5-5=3,5
odp podstawy trapez ają 8,5 i 3,5


20 3 20
2010-03-10T19:19:30+01:00
A-dłuższa podstawa
a-5cm-krótsza podstawa

P=18cm²
h=3cm

P=(a+b):2*h
18cm²=(a+a-5cm):2*3cm
18cm²=(2a-5cm):2*3cm
18cm²=(a-2,5cm)*3cm
3a-7,5cm=18cm²
3a=18cm+7,5cm
3a=25,5cm/:3
a=8,5cm-dłuższa podstawa

a-5cm=
8,5cm-5cm=
3,5cm-krótsza podstawa
odp.dłuższa podstawa ma 8,5cm,a krótsza 3,5cm
50 4 50